Identification of the Potential for Development of the Smart Village Concept in Sungai Buaya Village, Pemulutan District, Ogan Ilir Regency - Sumarnah, Sumarnah; Kencana, Novia; Kariem, M. Qur’anul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research was carried out with the aim of identifying the potential for developing the smart village concept in Sungai crocodile village, Pemulutan sub-district, Ogan Ilir district. Then the results of the analysis and findings in the field from this research show that the potential of Sungai crocodile village is optimal enough to develop from the status of progress and independence of "Developing" to "Advanced". This is based on analysis according to indicators according to Rachmawati in developing a more appropriate Smart village concept, namely 1. Smart government (smart governance), 2. Smart society (smart community), 3. Smart economy (smart economy) , and 4. Smart environment. The results of the research and discussion have shown that the conclusion obtained is that the Sungai crocodile village has quite optimal potential to develop from the status of progress and independence of "Developing" to "Advanced". There are several findings obtained during research, including the smart village concept which has been proposed to the government for a long time, in fact it does not match what exists on the ground, the reality is that this concept should be promoted to realize sustainable village development, in fact this concept is not the basis for current government programs. This public ignorance of this concept is enough proof of how far this concept has been developed.